Spatial Patterns of Inequality and Governance in Decentralising Indonesia, 1999-2014 - Isfandiarni S. Rosidin (Green Publisher Indonesia, 2025)
This paper presents the dynamic relationship between inequality and the quality of local governance at the district level, including a search for the main driving forces and spatial patterns of changes in this relationship. To this aim, we search for a systematic relationship between inequality and a set of governance indicators across districts throughout Indonesia. We find that the relationship between inequality and institutional quality is not straightforward, depending on which indicator we use as a proxy for the institutional variable. In contrast, we find that the relationship between inequality and governance is straightforward: good local governance is associated with low inequality at the district level. If we test for reverse causality, we find mixed evidence on the role of inequality as the determinant of local institutional quality. Reverse causality between inequality and governance is found when we use the service delivery index as a proxy for the governance variable: low inequality will improve local governance.